Computationally efficient methods for solving SURE models - Kontoghiorghes, Erricos John; Foschi, Paolo (My University, 2001)
Computationally efficient and numerically stable methods for solving Seemingly Unrelated Regression Equations (SURE) models are proposed. The iterative feasible generalized least squares estimator of SURE models where the regression equations have common exogenous variables is derived. At each iteration an estimator of the SURE model is obtained from the solution of a generalized linear least squares problem. The proposed methods, which have as a basic tool the generalized QR decomposition, are also found to be efficient in the general case where the number of linear independent regressors is smaller than the number of observations.
Keywords: Computational efficiency; Numerical analysis; Iterative methods; Generalized least squares estimators